Weighted Composition Operators from the Besov Spaces into the Bloch Spaces - Colonna, Flavia; Li, Songxiao (Bulletin of the Malaysian Mathematical Sciences Society, 2013)
Let ... be an analytic self-map of the open unit disk ... in the complex plane ... and let ... be a fixed analytic function on ... The weighted composition operator is defined on the space ... of analytic functions on ... by ... In this work, we characterize the bounded and the compact weighted composition operators from the Besov spaces ... (1< ... >∞) into the Bloch space as well as into the little Bloch space. 2010 Mathematics Subject Classification: Primary: 47B33, Secondary: 30H30 (ProQuest: ... denotes formulae omitted.)